Pengaruh Media Arang Kayu Bakau Mangrove Dan Arang Kayu Asam Pada Proses Perlakuan Carburizing Terhadap Sifat Mekanik Baja Karbon ST-37 - Arifandi, Rico; Pohan, Gerald Adityo (JURNAL FLYWHEEL, 2021)
In the military field, tank is armored fighting vehicles that move using chain-shaped wheels. The tread of the tank chain is a component to tread and move so that it requires tougher properties on the surface and has ductile and tough properties on the inside and is more resistant to wear on the surface. The development of tank chain production materials is necessary for the independence of national defense and security as well as reducing dependence on imports. Imported tank chain hardness value 28 HRC or 286 HV. In this research, the objective of this research is to increase the surface hardness of the steel by carburizing the initial material, especially the low carbon steel ST-37. The carburizing treatment process is a method of adding carbon content in steel using solid media. The carbon media used were mangrove charcoal and tamarind wood charcoal using calcium carbonate (CaCO3) catalyst at a constant heating temperature of 900ºC, variations in holding time of 30 minutes, 60 minutes and 90 minutes, cooled rapidly with water media. Then performed an analysis of the effect of the type of wood charcoal on the mechanical properties of carbon steel ST-37. The results obtained will be applied to the tank chain tread production process. The results of the micro structure of martensite and the highest hardness value were found in the holding time of 60 minutes of mangrove charcoal media with the microstructure results of 63.8% martensite, 36.2% bainite and a hardness value of 453.1 HV. The highest toughness value is found in the holding time of 60 minutes of tamarind wood charcoal media with an impact price (HI) of 0.4345 J/mm2. The difference between the impact test results of tamarind charcoal media with mangroves is not too significant. The higher the martensite phase, the higher the hardness value. However, there is also a bainite phase which can increase the toughness of the steel which will be used as a tread chain production material.